Participation of Students with Hearing Impairment in Inclusive Classes - Siti Musayaroh; Imas Diana Aprilia (Journal of ICSAR, 2018)
One indicator of the success of the learning process is the active role of all students. The aim of this study was to find out how the participation of students with hearing impairment during learning process in inclusive classes. This research use descriptive method. Three students with hearing impairment have been selected according to predefined criteria. The data was collected by observation, interview and documentation. The data were analyzed through data reduction, data display and conclusion or verification. The results show that participation of students with hearing impairment during the learning process in inclusive classes is not very active. The way teachers teach, the lack of their understanding on learning materials and the presence of other special needs students in same classes influences their active participation during the learning process in the inclusive classes.